Chemical Interaction between the Sr4Al6O12SO4 Ceramic Substrate and Al–Si Alloys - José Amparo Rodríguez-García; Carlos Adrián Calles-Arriaga; Ricardo Daniel López-García; José Adalberto Castillo-Robles; Enrique Rocha-Rangel (Eng, 2024)
Samples of Sr4Al6O12SO4 are obtained through a solid-state reaction of Al2O3, SrSO4, and SrCO3. The samples are then made into 1 and 4 cm pellets by compacting them at 100MPa and sintering them at 1400 °C for 4 h. The compound is analyzed using X-ray diffraction. Static immersion and wettability tests are carried out to evaluate corrosion resistance in contact with Al–Si. Corrosion tests are conducted by immersing the samples at 800, 900, and 1000 °C for 24, 50, and 100 h, while wettability is studied at 900, 1000, and 1100 °C for 2 h. Afterwards, the samples are subject to metallographic preparation. The samples are then analyzed using optical microscopy, scanning electron microscopy, and image analysis. In general, reaction products consisting of alumina, spinel, oxides, and sulfates are found. The contact angles obtained are between 124° and 135°. It is concluded that the Sr4Al6O12SO4 ceramic substrate is resistant to corrosion by the Al–Si alloy because of the slight thickness of the reaction products found in the samples (73 μm), considering the severe conditions of the experiment: 1000 °C and 100 h of isothermal temperature. Furthermore, Sr4Al6O12SO4 is not wettable by Al–Si alloys. These results suggest that the ceramic substrate could be used in the refractory industry, possibly as an additive to commercial refractory ceramics. For future work, it is recommended to carry out the same study with the aluminum–magnesium alloy and as an additive in commercial refractory ceramics.